Journey in time and space - NEHMÉ, Edgard (International Arab Journal of Dentistry (IAJD), 2020)
If it is terrifying to think that life can be at the mercy of the multiplication of these infinitely small, it is also comforting to hope that science will not always remain powerless in front of such enemies. Louis Pasteur Chemist, founder of medical microbiology